Case report on spontaneous ovarian hyperstimulation syndrome following natural conception associated with primary hypothyroidism - Smisha Sridev; Sridev Barathan (Wolters Kluwer Medknow Publications, 2013)
Spontaneous OHSS is a rare event in pregnancy following natural conception and only a few cases have been reported in the literature so far. This report is a case of spontaneously conceived pregnancy with Spontaneous OHSS and Primary hypothyroidism